2015
DOI: 10.1002/etc.2884
|View full text |Cite
|
Sign up to set email alerts
|

Copper-induced root growth inhibition of Allium cepa var. agrogarum L. involves disturbances in cell division and DNA damage

Abstract: Copper (Cu) is considered to be an indispensable microelement for plants. Excessive Cu, however, is toxic and disturbs several processes in the plant. The present study addressed the effects of ionic Cu (2.0 µM and 8.0 µM) on mitosis, the microtubule cytoskeleton, and DNA in root tip cells of Allium cepa var. agrogarum L. to better understand Cu toxicity on plant root systems. The results indicated that Cu accumulated in roots and that root growth was inhibited dramatically in Cu treatment groups. Chromosomal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 38 publications
3
33
0
Order By: Relevance
“…4A), contradicting data found by d' Aquino et al (2009). In general, toxicity symptoms caused by trace elements in plants include the induction of chromosomal aberrations linked to the inhibition of the mitotic index (d' Aquino et al, 2009;Qin et al, 2015). Although the induction of chromosomal abnormalities was shown in the present study, the mitotic index was increased because La induced cell division.…”
Section: Tablementioning
confidence: 44%
“…4A), contradicting data found by d' Aquino et al (2009). In general, toxicity symptoms caused by trace elements in plants include the induction of chromosomal aberrations linked to the inhibition of the mitotic index (d' Aquino et al, 2009;Qin et al, 2015). Although the induction of chromosomal abnormalities was shown in the present study, the mitotic index was increased because La induced cell division.…”
Section: Tablementioning
confidence: 44%
“…Heavy metal toxicity induces chromosomal aberrations and also decreases the cell division rate. A number of studies have previously identified heavy metal induced nucleic acid impairments in plants like Allium cepa (Steinkellner et al, 1998;Barbosa et al, 2010;Arya et al, 2013;Arya and Mukherjee, 2014;Qin et al, 2015), Vicia faba (Qun and Xiao, 1995;Steinkellner et al, 1998;Marcato-Romain et al, 2009;Pourrut et al, 2011;Arya et al, 2013;Arya and Mukherjee, 2014), Helainthus annuus (Chakravarty and Srivastava, 1992), Solanum tuberosum, and Nicotiana tabacum (Gichner et al, 2006) etc. Genotoxic responses differ among plant species to the same metal and usually depends on the number and total length of the diploid chromosomes and also the number of metacentric chromosomes (Ma et al, 1995;Patra et al, 2004).…”
Section: Genotoxicitymentioning
confidence: 99%
“…Similarly, Hirata et al (2011) identified Cr and As induced translesion DNA synthesis resulting due to generation of 8-OHdG. Qin et al (2015) studied genotoxic effects of copper (Cu) in root tip cells of A. cepa var. agrogarum L. The exposure to ionization Cu led to reduced mitotic index and chromosomal aberrations (viz.…”
Section: Genotoxicitymentioning
confidence: 99%
“…The growth stimulation may be explained in part due to the inducement of cell proliferation (de Oliveira et al 2015), as well as due to the increase in the efficiency of photosystem II photo chemistry and electron transport rate by REEs (Wang et al 2006). However, the damage to plant growth in higher REEs treatments results in the inhibition of the mitotic index (Qin et al 2015;d'Aquino et al 2009) and the inducement of DNA breakage and DNA-protein crosslinks (DPCs) (Wang et al 2012). The decrease in the uptake of major elements, such as Mg and P, under the high REE treatments (Table 1) may also be partly responsible for the reduction in biomass of P. americana.…”
Section: The Effects Of Rees On Biomass and Ree Accumulation In Phytomentioning
confidence: 99%